Analysis of mural paintings using in situ non‐invasive XRF, FTIR spectroscopy and optical microscopy. (30th May 2013) - Vornicu, Nicoleta; Bibire, Cristina; Murariu, Elena; Ivanov, Daniela
Abstract : An analytical protocol consisting of X‐ray fluorescence spectroscopy, optical microscopy and Fourier transform infrared spectroscopy was used to study the origin and the nature of the materials (pigments, binders and coating preparation) of the Fundenii Doamnei church mural paint from Bucharest. The main interest of the present study consisted in the original votive paint from narthex, painted in 1757 in a secco technique. During analysis, an unexpected pigment in the votive paint could be detected by the combined analytical techniques: ultramarine blue. Along with this pigment, the presence of gypsum binder based on egg and flax seed oil could also be evidenced. These results demonstrated a secco execution technique of the votive paint and also the presence of a restoration treatment. Moreover, during the present study, the components of the preparation layer and the constitutive pigments from both 1699 and 1757 years mural paints have been analyzed. Hence, the following pigments could be identified: vermilion, azurite, cinnabar, lead white, ochre, natural umber and gold, by using the combination of the analytical techniques. The novelty of our results consists in detecting the composition of the materials used in this church painting ( fresco and a secco ) during these 254 years since its first restoration. The results of these investigations pointed to the suitability of the non‐destructive and semi‐destructive analytical techniques in the complex characterization of the paints realized in different techniques, at different periods. Copyright © 2013 John Wiley & Sons, Ltd.